Mosaicos de Belém: história e conservação - TOSCANO, Thais Zumero (Universidade Federal do Pará, 2017)
The mosaic is an ancient art which impacts the history of civilizations. The city of Belém po-sesses a beautiful, peculiar and rare acquis. For being so uncommon, it is not regarded as an autonomous or as well integrated art. This fact becomes visible due to the lack of biblio-graphical data and registries on the theme. This research aims to demonstrate such facts by means of a historical contextualization and a literature review that covers techniques, con-servation, common damages and frequent pathological conditions. The main focus of this study is the mosaic collection of the city of Belém /Pará. It identifies techniques, typologies, datings, physical constitutive characteristics of the employed materials. Materials and me-thods are presented starting from the samples selected. After the analysis of these samples with their features and physical chracateristics by optic microscopy the study comes to its final part, the conclusions based on the necessary preservation of this cultural asset which integrates the memory of the city.